A feedback-based model for CSR assessment and materiality analysis. Issue 4 (December 2015) - Calabrese, Armando; Costa, Roberta; Rosati, Francesco
Highlights: The model provides the assessment of three aspects of CSR commitment. The model profiles customers on the basis of their CSR feedback. Customer feedback is assessed basing on CSR expectations and perceptions. The model is highly suited for use in CSR evaluation and strategic planning. The model provides a valuable instrument for materiality analysis. Abstract: Current CSR literature offers little insight into how to engage customers and other stakeholders about their CSR expectations and perceptions. The aim of this paper is to propose a model for CSR evaluation and planning based on the classification of customer CSR feedback through the comparison of three aspects of CSR commitment (disclosed, perceived and expected). Although the paper is focused on customers, the model can be applied indifferently to any stakeholder group, thus providing a valuable instrument for materiality analysis and stakeholder engagement. In effect, the model allows identifying material CSR issues regarding all stakeholder perceptions and expectations.